KEBERLANJUTAN PENYADAPAN GETAH POHON PINUS DI DESA BAYUNG KECAMATAN SEBERANG MUSI, KABUPATEN KEPAHIANG, BENGKULU - Cahyadi Insan; Agus Susatya; Ridwan Yahya (Universitas Lambung Mangkurat, 2021)
Sustainability in managing natural resources depends on the availability of current and future resources within management schemes. Tapping Pine trees for resin production have long been practiced in Bukit Daun Protection Forest, Kepahiang, Bengkulu, despite Bengkulu has not been known as a main province producing pine’s resin. Therefore, it was worthily to examine the sustainability of managing pine stand for production of pine’s resin at Bayung, Seberang Musi, Kepahiang, Bengkulu. The research was carried out with Multi Dimensional Scaling (MDS) approach and using Rapid Appraisal for Tapping Pine Trees (RP-TPT) software. It was constructed by ecologiy, economy, Social and culture, law dan institution, and technology and infrastructure dimensions. Ten attributes were assigned to each dimension. The result indicated that the managing pine stand was moderately sustainable (57.66). All dimensions were categorized into moderately sustainable, except to technology and infrastructure dimension (48.15), which was classified as poorly sustainable. Among 50 attributes, sixteen attributes were grouped as sensitive, meaning they are strongly influential to the sustainability to pine’s resin production. Sustainability could be increased by management intervention, especially to the improvement of tapping’s kill attribute of the technology and infrasrtucture dimension. This management intervention should also be followed by the improvement of the other attributes.